Antecedents and Outcomes of Corporate Social Investment on Customer Loyalty: A Case of Zimbabwe Stock Exchange Listed Companies - Nkala, Doreen (Midlands State University, 2022)
Corporate Social Investment (CSI) is a relatively new philosophy employed by corporates to build a strong bond within the communities in which they operate. Firms invest in several communities based on sustainable development initiatives for the good of humanity. The thin line between CSI and corporate social responsibility is primarily anchored on levels of commitment and intention. While CSR is more of a public relations activity, CSI is proactive and aims to change and improve community livelihoods. The objective of this study was to examine the determinants and outcomes of CSI on companies listed on the Zimbabwe Stock Exchange. This was necessitated by the increased demand by several stakeholders, including customers, investors, government and communities, for companies to increase their CSI participation. Companies listed on the Zimbabwe Stock Exchange represent various sectors and have a broader capital base, hence, the deliberate efforts to focus on them. It became imperative that particular focus be directed on the effects of CSI on corporate image, customer trust and customer loyalty. Primary data was gathered from a target population of 1200 senior managers and sample data of 252 companies seeking to determine the number of issues amongst them, sector type, year of establishment, the number of employees, total assets, and capital flows in the past five years. The Structural Equation Modelling approach was used, SMARTPLS software was chosen for hypotheses testing, and the model fit to accommodate the sample size. Results showed that CSI positively affected community, customer, investor, environmental, and government demands. Findings showed that CSI positively affected corporate reputation, customer trust, and loyalty. The study significantly contributed to the existing knowledge on CSI regarding Zimbabwe Stock Listed Companies. The study recommends that Zimbabwe Stock Exchange regulators develop policies that enhance corporates' increased CSI initiatives. Managers could use Integrated Marketing Communication to update stakeholders from time to time.